Collagen IV-β1-Integrin Influences INS-1 Cell Insulin Secretion via Enhanced SNARE Protein Expression - Barillaro, Malina; Schuurman, Meg; Wang, Rennian (Frontiers in Cell and Developmental Biology, 2022)
b1-integrin is a key receptor that regulates cell-ECM interactions and is important in maintaining mature beta-cell functions, including insulin secretion. However, there is little reported about the relationship between ECM-b1-integrin interactions and exocytotic proteins involved in glucose-stimulated insulin secretion (GSIS). This study examined the effect of collagen IV-b1-integrin on exocytotic proteins (Munc18-1, Snap25 and Vamp2) involved in insulin secretion using rat insulinoma (INS-1) cell line. Cells cultured on collagen IV (COL IV) had promoted INS-1 cell focal adhesions and GSIS. These cells also displayed changes in levels and localization of 1-integrin associated downstream signals and exocytotic proteins involved in insulin secretion. Antibody blocking of b1-integrin on INS-1 cells cultured on COL IV showed significantly reduced cell adhesion, spreading and insulin secretion along with reduced exocytotic protein levels. Blocking of b1-integrin additionally influenced the cellular localization of exocytotic proteins during the time of GSIS. These results indicate that specific collagen IV-b1-integrin interactions are critical for proper beta-cell insulin secretion.